2022
DOI: 10.1007/s42242-022-00210-6
|View full text |Cite
|
Sign up to set email alerts
|

Designs and methodologies to recreate in vitro human gut microbiota models

Abstract: The human gut microbiota is widely considered to be a metabolic organ hidden within our bodies, playing a crucial role in the host’s physiology. Several factors affect its composition, so a wide variety of microbes residing in the gut are present in the world population. Individual excessive imbalances in microbial composition are often associated with human disorders and pathologies, and new investigative strategies to gain insight into these pathologies and define pharmaceutical therapies for their treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 183 publications
1
4
0
Order By: Relevance
“…This observation aligns with a prior study that reported low variability among 3D organoids derived from multiple human donors (Mohammadi et al, 2021). A possible explanation for the similarity observed between donors is that RepliGut® Planar does not contain an intestinal microbiome or immune cells, both of which are significant variables among humans that can influence clinical outcomes (Parlesak, 2004;Trujillo-de Santiago et al, 2018;Khan et al, 2019;Biagini et al, 2023). Developing strategies to model host-microbe interactions in RepliGut® Planar is a promising next step to enhance the clinical relevance and translatability of this platform.…”
Section: Discussionsupporting
confidence: 86%
“…This observation aligns with a prior study that reported low variability among 3D organoids derived from multiple human donors (Mohammadi et al, 2021). A possible explanation for the similarity observed between donors is that RepliGut® Planar does not contain an intestinal microbiome or immune cells, both of which are significant variables among humans that can influence clinical outcomes (Parlesak, 2004;Trujillo-de Santiago et al, 2018;Khan et al, 2019;Biagini et al, 2023). Developing strategies to model host-microbe interactions in RepliGut® Planar is a promising next step to enhance the clinical relevance and translatability of this platform.…”
Section: Discussionsupporting
confidence: 86%
“…Among the known disadvantages of short-term and non-dynamic experiments are the limited nutrient availability and accumulation of metabolic waste products [ 3 , 5 ]. We limited this study to 48 h due to our previous experiences that showed us that 24 h was sufficient to reach a relative stabilization of the microbial communities present in the batch systems and that not many differences are commonly observed when compared to 48 h and 72 h in terms of metabolic production and microbial content [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Batch culture or static colonic fermentation models are popular screening experiments conducted in individual bioreactors where the test substance is maintained in contact with microbial communities and basal media. These assays are generally performed for short durations, ranging from 24 to 48 h, with a maximum of 72 h. Several parameters can be controlled, including pH, temperature, and the maintenance of an anaerobic atmosphere [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is currently a lack of in vitro studies investigating whether and how salidroside selectively alters bacterial function or competitiveness. In-vitro models of the human gut microbiota, such as Transwell culture models ( Biagini et al, 2023 ), could be an effective approach to delineate the specific mechanisms through which salidroside protects against atherosclerosis by interacting with the gut microbiota and its metabolites.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%